Gut microbiota-dependent trimethylamine n-oxide pathway contributes to the bidirectional relationship between intestinal inflammation and periodontitis - Wang, Qiqi; Sun, Yue; Zhou, Tianyu; Jiang, Cong; A, Lan; Xu, Wenzhou (Frontiers in Cellular and Infection Microbiology, 2023)
Background Intestinal inflammation and periodontitis influence the development of each other through the bidirectional relationship. As the intestinal microbiome metabolite, trimethylamine-N-oxide (TMAO) could contribute to chronic inflammation in the gut by influencing the gut microbial composition and intestinal immunity. Increased circulating TMAO levels often accompany clinical findings in patients with experimental periodontitis. However, the role of TMAO in the bidirectional relationship between intestinal inflammation and periodontitis remains unclear. Thus, we explored whether TMAO influences the periodontitis process by affecting intestinal immunity and microbial composition in this article. Methods Periodontitis was induced by unilateral ligation of the first molar in mice, and 3,3-dimethyl-1-butanol (DMB) was used as an inhibitor to reduce TMAO circulating. Twenty-five BALB/c mice were randomly assigned to five study sets (n = 5/group): no periodontitis with DMB (Control group), periodontitis (P) group, periodontitis with TMAO (P+TMAO) group, periodontitis with TMAO and DMB (P+TMAO+DMB) group, and periodontitis with DMB (P+DMB) group. The effect of TMAO was determined by assessing changes in intestinal histology, intestinal flora composition, periodontal tissue, and periodontal pro-inflammatory factors at ten days. Results The outcomes indicated a marked improvement in the intestinal inflammation severity, and intestinal flora diversity was reduced. Firmicutes number and the ratio of Firmicutes/Bacteroidetes were improved in the P+TMAO group. In addition, the alveolar bone resorption and the degree of periodontal tissue inflammation were more severe in the P+TMAO group than in other groups. Immunohistochemistry showed higher levels of TGF-β and IL-1β expression in the periodontal tissues of P+TMAO. Conclusions Our data suggest that TMAO could influence periodontal immunity and promote periodontal inflammation by affecting the intestinal microenvironment, revealing TMAO may affect the development of periodontitis through the bidirectional relationship of the oral-gut axis.